Fundamental Structure of General Stochastic Dynamical Systems: High-Dimension Case - Haoyu Wang; Xiaoliang Gan; Wenqing Hu; Ping Ao (Journal of Mathematics)
No one has proved that mathematically general stochastic dynamical systems have a special structure. Thus, we introduce a structure of a general stochastic dynamical system. According to scientific understanding, we assert that its deterministic part can be decomposed into three significant parts: the gradient of the potential function, friction matrix and Lorenz matrix. Our previous work proved this structure for the low-dimension case. In this paper, we prove this structure for the high-dimension case. Hence, this structure of general stochastic dynamical systems is fundamental.